Investigating the use of neurorehabilitation scales in paediatric neurosurgical patients at a tertiary academic hospital in Gauteng - Padayachy, Prof. L.C (University of Pretoria, 2024)
Dissertation (MSc(Human Physiology))--University of Pretoria 2024.